S17.2 Hpv infection, genital inflammation, and hiv risk in the caprisa 004 trial. (13th September 2015) - Karim, Quarraisha Abdool; Liebenberg, Lenine J; Leask, Kerry; Samsunder, Natasha; Kharsany, Ayesha; Grobler, Anneke; McKinnon, Lyle; Passmore, Jo-Ann; Karim, Salim Abdool
Abstract : There is a growing body of data demonstrating an increased risk for HIV acquisition in the presence of HPV infection, but the mechanism of this relationship is unclear. This study investigated the impact of HPV infection on both genital inflammation and HIV risk in the CAPRISA 004 1% TFV gel trial. Baseline cervicovaginal lavage specimens collected from 737 HIV-uninfected women were analysed to determine the prevalence of HPV infection. Clinical, reproductive, demographic and behavioral data were captured. The presence of DNA from 37 HPV genotypes was assessed using Linear Array, and the concentrations of 48 relevant cytokines were quantified by multiplexed ELISA assays. The presence of HIV was measured monthly using two rapid tests and confirmed by western blot and PCR. Of the 737 eligible participants, 74% had prevalent HPV-infection (95% CI: 71–77%). Participants with prevalent HPV infection were 2.8 times more likely to acquire HIV infection compared to those with no HPV infection (95% CI: 1.3–5.9; p = 0.007). HIV risk was independent of the oncogenicity of HPV strains at baseline [(HPV oncogenic strains HR 2.5 (95% CI 1.0–6.2) vs non-oncogenic strains HR 2.1 (95% CI 0.9–5.1)], and was also increased in the presence of multiple concurrent infections (HR 3.1; 95% CI 1.4–6.8). No cytokine signatures were associated with prevalent HPV infection. The use of tenofovir gel did not prevent HPV infection. These data confirm a relationship between HPV infection and increased risk for HIV acquisition, and underscores the need to define the underlying biological mechanisms to inform targeted interventions in settings that bear a high burden of both infections.